Bibliometric analysis on authentic leadership - Abdul Aziz, Nor Azni; Asimiran, Soaib; Abdullah, Arnida; Mahazir, Masturina (Kalahari Journals, 2022)
Studies on school leadership have proven that effective leadership is crucial for improving school outcomes. School leaders have an indirect impact on students’ learning performance through their roles in influencing the teachers’ attitudes and behaviour outcomes. Leaders with authentic leadership portray good values, lead with integrity, motivate their employees and be transparent with their intention, leading to desirable work attitudes and behaviours. This paper aimed to provide a detailed analysis of bibliometric review on authentic leadership with Publish or Perish software for incorporating the obtained data. Meanwhile, VOSviewer was employed for data visualization, and the Scopus database was utilized to collect all literature in authentic leadership. A total of 706 articles were clarified and evaluated from various authentic and qualified journals starting from 1997 to 2021 (24 years). The studies related to authentic leadership have a significant increase from the earliest 2 in 1997 to 100 articles in 2020. The United States of America, Canada, and United Kingdom made the three most contributions to the literature associated with authentic leadership research, while the top journal was Leadership Quarterly. Findings indicated that the numbers of related research on authentic leadership in the educational field were limited compared to other fields. Therefore, researchers and practitioners should give more attention to developing and improving the research on authentic leadership.